Substituting dietary monounsaturated fat for saturated fat is associated with increased daily physical activity and resting energy expenditure and with changes in mood(1)(2)(3) - Kien, C Lawrence (American Society for Nutrition, 2013)
Background: The Western diet increases risk of metabolic disease. Objective: We determined whether lowering the ratio of saturated fatty acids to monounsaturated fatty acids in the Western diet would affect physical activity and energy expenditure. Design: With the use of a balanced design, 2 cohorts of 18 and 14 young adults were enrolled in separate randomized, double-masked, crossover trials that compared a 3-wk high–palmitic acid diet (HPA; similar to the Western diet fat composition) to a low–palmitic acid and high–oleic acid diet (HOA; similar to the Mediterranean diet fat composition). All foods were provided by the investigators, and the palmitic acid (PA):oleic acid (OA) ratio was manipulated by adding different oil blends to the same foods. In both cohorts, we assessed physical activity (monitored continuously by using accelerometry) and resting energy expenditure (REE). To gain insight into a possible mood disturbance that might explain changes in physical activity, the Profile of Mood States (POMS) was administered in cohort 2. Results: Physical activity was higher during the HOA than during the HPA in 15 of 17 subjects in cohort 1 (P = 0.008) (mean: 12% higher; P = 0.003) and in 12 of 12 subjects in the second, confirmatory cohort (P = 0.005) (mean: 15% higher; P = 0.003). When the HOA was compared with the HPA, REE measured during the fed state was 3% higher for cohort 1 (P < 0.01), and REE was 4.5% higher in the fasted state for cohort 2 (P = 0.04). POMS testing showed that the anger-hostility score was significantly higher during the HPA (P = 0.007). Conclusions: The replacement of dietary PA with OA was associated with increased physical activity and REE and less anger. Besides presumed effects on mitochondrial function (increased REE), the dietary PA:OA ratio appears to affect behavior. The second cohort was derived from a study that was registered at clinicaltrials.gov as R01DK082803.